2015
DOI: 10.3354/aei00128
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of supplementation aquaculture on the genetic diversity of wild Ruditapes decussatus from northern Spain

Abstract: The European carpet shell Ruditapes decussatus is among the most important shellfish species cultured in estuaries and bays of the northern Iberian Peninsula. Increased demand and overfishing of native R. decussatus, as well as irregular yields due in part to pollution and urban sprawl, have led to overexploitation of the species and to the import of the non-indigenous R. philippinarum in the early 1980s. In recent years, supplementation aquaculture of R. decussatus (supportive breeding) has been implemented a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 51 publications
2
27
0
1
Order By: Relevance
“…Hybridization between the two species also imposes identification problems. For example, the introgressed genetic marker was found in individual specimens of apparent morphologically pure phenotypes, whereas individual specimens with intermediate morphology were genetically determined to be a pure species (Habtemariam et al 2015). Genetic analyses confirmed that the aforementioned morphological and morphometric characteristics can be soundly applied to differentiate between Ruditapes philippinarum and Ruditapes decussatus.…”
Section: Differentiation: R Philippinarum and R Decussatusmentioning
confidence: 83%
See 1 more Smart Citation
“…Hybridization between the two species also imposes identification problems. For example, the introgressed genetic marker was found in individual specimens of apparent morphologically pure phenotypes, whereas individual specimens with intermediate morphology were genetically determined to be a pure species (Habtemariam et al 2015). Genetic analyses confirmed that the aforementioned morphological and morphometric characteristics can be soundly applied to differentiate between Ruditapes philippinarum and Ruditapes decussatus.…”
Section: Differentiation: R Philippinarum and R Decussatusmentioning
confidence: 83%
“…Hybrids between the allochthonous R. philippinarum and the autochthonous R. decussatus have been found in the north west and north of Spain (Hurtado et al 2011, Habtemariam et al 2015. As hybridization might lead to the local extinction of R. decussatus in areas where R. philippinarum is intentionally introduced to enhance commercial harvesting, Habtemariam et al (2015) suggested prohibiting the release of the alien R. philippinarum into natural waters as well as selecting non-hybridized R. decussatus for repopulation of overexploited areas. Hybridization between the two species also imposes identification problems.…”
Section: Differentiation: R Philippinarum and R Decussatusmentioning
confidence: 99%
“…; Habtemariam et al. ). However, only two studies have sampled a significant number of populations (Borsa et al.…”
Section: Introductionmentioning
confidence: 97%
“…The syndrome of ecological problems caused by invasive species is emerging in places where the Manila clam has established. This include an increase of clam numbers and the displacement of native species162326272829, but also, in Europe, hybridization with the native clam R. decussatus and subsequent introgression3031.…”
mentioning
confidence: 99%